Analisis Efektivitas Pad Dan Upaya Peningkatan Di Kabupaten Bungo Tahun 2007- 2012 - Wahyu Pangestuning Margono (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2016)
Revenues derived from regional tax revenues and levies, regionally owned company (BUMD) revenues and other legitimate revenues collected by Bungo regional regulations in accordance with the law are calculated in dollars. In running the government to achieve development, the regional government needs a source of PAD, taxes, regional levies, company profits, other legitimate income. The research was conducted at Bungo. The data used is a secondary data source through the realization of revenue in the area of ​​the Bungo Revenue Service and Asset Management (DPPKA) office and the Bungo Central Bureau of Statistics (BPS). This research is a quantitative research. These results indicate that local taxes, affluent levies, (company) profits, make a small contribution to strip income, and that the contribution is large to other legitimate revenues. However, the level of effectiveness is very effective with an average of 102.23%. However, it must be mentioned that the improvement is the result of maximizing PAD revenue. Based on this research, it can be suggested to the government to formulate appropriate policies that will lead to the development of increased local and regional original incom